2016
DOI: 10.15376/biores.11.4.8239-8256
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Step Conversion of Corn Stover into Furfural and Levulinic Acid in a Water/Gamma-Valerolactone System

Abstract: A two-step hydrolysis method was evaluated as a potential means of obtaining high yields of furfural and levulinic acid from corn stover using sulfuric acid as catalyst in a water/gamma-valerolactone (GVL) system. The corn stover underwent a high-temperature hydrolysis process to produce levulinic acid, followed by a low-temperature hydrolysis process to produce furfural. A series of experiments were conducted to explore the relationship between the different reaction parameters and the final yields of furfura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…In our previous research, it was reported that H 2 SO 4 shows a much higher selectivity on cellulose conversion to LA than HCl with corn stover used as the substrate, while HCl performs better than H 2 SO 4 in HMF production. 40 In this study, the different catalytic effects of HCl and H 2 SO 4 to transform glucose to HMF were further assessed in the water/GVL system, and different types of alkali metal salts were tested to decide the suitable additive used to further enhance the HMF yield. In addition, various reaction parameters, including reaction temperature, reaction time, acid concentration and salt dosage were investigated to determine the optimal conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous research, it was reported that H 2 SO 4 shows a much higher selectivity on cellulose conversion to LA than HCl with corn stover used as the substrate, while HCl performs better than H 2 SO 4 in HMF production. 40 In this study, the different catalytic effects of HCl and H 2 SO 4 to transform glucose to HMF were further assessed in the water/GVL system, and different types of alkali metal salts were tested to decide the suitable additive used to further enhance the HMF yield. In addition, various reaction parameters, including reaction temperature, reaction time, acid concentration and salt dosage were investigated to determine the optimal conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In CS F , some catalysts were used to hydrolyze hemicellulose, and fructose was not completely converted to HMF and levulinic acid. The reason for this is that the optimal reaction conditions for furfural in the one-pot process may result in a very low yield of levulinic acid, leading to the degradation of furfural …”
Section: Resultsmentioning
confidence: 99%
“…The reason for this is that the optimal reaction conditions for furfural in the one-pot process may result in a very low yield of levulinic acid, leading to the degradation of furfural. 37 4. CONCLUSIONS This study showed that the structure of Fenton-modified CS in the batch reaction was destroyed and the holocellulose loss was large.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, one of the biomass-originated, green solvents c-valerolactone (GVL), which is currently present in a wide range of food and cosmetic products, was introduced by Horva ´th et al ( 2008) as a sustainable liquid for chemical conversion, and proposed by Fang and Sixta (2014) as a solvent for biomass pulping (Fang and Sixta 2014;Horva ´th et al 2008). Since then, several research groups tested the capability of GVL for the fractionation of biomass at acid-catalyzed conditions at mild temperatures or of agricultural waste and its transformation to furfural and fermentable sugars (Alonso et al 2017;Li et al 2016;Qing et al 2018;Shuai et al 2016).…”
Section: Introductionmentioning
confidence: 99%